The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1177/21582440211016557
|View full text |Cite
|
Sign up to set email alerts
|

Does Governance in Information Technology Matter When It Comes to Organizational Performance in Pakistani Public Sector Organizations? Mediating Effect of Innovation

Abstract: Information technology governance (ITG) is recognized as a vital organizational ability to exploit opportunities for innovation and enhance organizational performance. However, the potential of ITG for public sector innovation and performance has not been fully grasped in Pakistani public sector organizations (PakPSOs). This study has presented an explanatory model to investigate the mediating effect of innovation in the relationship between ITG and organizational performance in PakPSOs. Partial least squares … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…First, adopt the Hamann one-way test. Put all latent variables into the factor analysis without rotation, and observe whether the principal component of the first precipitation is lower than 50% ( Ali et al, 2021 ). The results showed that the first principal component explanation accounted for 34.48%, so the Hamann one-way test passed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…First, adopt the Hamann one-way test. Put all latent variables into the factor analysis without rotation, and observe whether the principal component of the first precipitation is lower than 50% ( Ali et al, 2021 ). The results showed that the first principal component explanation accounted for 34.48%, so the Hamann one-way test passed.…”
Section: Resultsmentioning
confidence: 99%
“…When knowledge redundancy arises, enterprises will take the initiative to reintegrate the current workforce or set up a rotation system to establish a good talent flow ( Scott, 2012 ), which prompts employees to unshackle themselves from rigid thinking and increase their intrinsic motivation to innovation. Additionally, we hold that the essence of innovation is to generate new ideas and opportunities through the progressive accumulation and recombination of existing and new knowledge ( Ali et al, 2021 ), in the process of job rotation, innovative employees can acquire varied and complex knowledge, enhance their technological innovation ability and promote exploratory innovation.…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%
“…Innovation enables organizations to establish conditions for structural, processes, management systems, and product/service improvements (Ali et al, 2021) and therefore, enhances productivity and financial outcomes in organizations (Ni et al, 2020). Innovation is beneficial to organizations at various organizational levels.…”
Section: Innovation and Organizational Performancementioning
confidence: 99%
“…Other researchers utilized innovation as an independent variable and employed other perspectives of innovation and found that innovation leads toward improved OP (Bowen et al, 2010; Tuan et al, 2016). Researchers also employed different perspectives of innovation as mediators and moderators with wide variety of independent and dependent variables (AlAnazi et al, 2021; Ali et al, 2021; R. Li et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…For example, they would appreciate and foster employee creativity in generating new products and providing new and innovative ideas. Previously, some scholars studied strategic flexibility as a significant factor affecting firm performance (Awais et al, 2023;Gorondutse et al, 2021). Some studied it as a mediator for certain relationships (Jian et al, 2023;Sen et al, 2023).…”
Section: Introductionmentioning
confidence: 99%